Pomiar ryzyka modelu w wycenie opcji - Kuziak, Katarzyna (Model risk valuation in option pricing, 2006)
Empirical research conducted in index option pricing models pointed out that results are very sensitive to assumptions laying upon them and necessity of managing this type of risk. One of the steps in risk management process is the risk measurement. For the options good risk measure is vega coefficient (first derivative of the option value with respect to volatility of underlying). Models risk measurement in the index option pricing area was illustrated with estimation error example (bad specification of stochastic process for the rate of return). Vega coefficients were calculated based on market prices also. So called empirical vega do not show any regularities and it is not characterized by the same properties as vega coefficient which is calculated from the models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 93-102